2022
DOI: 10.3390/ijms23063264
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular High-Mobility Group Box-1 as a Therapeutic Target of Gastric Cancer

Abstract: Background: High-mobility group box-1 (HMGB1) is involved in the tumorigenesis and metastasis of various cancers. The present study investigated the roles of extracellular HMGB1 in the progression of gastric cancer (GC) and the therapeutic effects of recombinant human soluble thrombomodulin (rTM) targeting HMGB1. Methods: The effects of extracellular HMGB1 and rTM on GC cells were assessed using proliferation and Transwell assays. Their effects on local tumor growth and metastasis were evaluated using subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…By overlapping the results of analysis, we found 6 genes exhibiting possibly regulated by miR - 665 : HMGB1 , limb and CNS expressed 1 like ( LIX1L ), calcium regulated heat stable protein 1 ( CARHSP1 ), proteasome inhibitor subunit 1 ( PSMF1 ), solute carrier family 37 member 3 ( SLC37A3 ), and synaptotagmin 2 ( SYT2 ) ( Figure 4A ). Among these genes, only HMGB1 was reported to be involved in the progression of GC ( 24 , 25 ). Thus, we chose HMGB1 as the target gene of miR - 665 in subsequent study.…”
Section: Resultsmentioning
confidence: 99%
“…By overlapping the results of analysis, we found 6 genes exhibiting possibly regulated by miR - 665 : HMGB1 , limb and CNS expressed 1 like ( LIX1L ), calcium regulated heat stable protein 1 ( CARHSP1 ), proteasome inhibitor subunit 1 ( PSMF1 ), solute carrier family 37 member 3 ( SLC37A3 ), and synaptotagmin 2 ( SYT2 ) ( Figure 4A ). Among these genes, only HMGB1 was reported to be involved in the progression of GC ( 24 , 25 ). Thus, we chose HMGB1 as the target gene of miR - 665 in subsequent study.…”
Section: Resultsmentioning
confidence: 99%
“…HMGB-1 has been identified as a proinflammatory mediator and is expressed twofold more in adipose tissue from obese compared to normal-weight individuals 32 . It was reported to interact with the NF-κB pathway to initiate the transcription of various proinflammatory cytokines including TNF-α, IL-6, and IL-1b to promote inflammation 33 , 34 . In clinical settings, Osoegawa et al demonstrated that higher surgical invasion increased the concentration of postoperative plasma HMGB-1 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In the stomach under physiological conditions, HMGB1 is mainly localized in the nucleus and cytoplasm of gastric epithelial cells ( 39 ) and is involved in transcriptional regulation as a chromatin-binding factor associated with specific DNA-binding proteins ( 158 , 159 ). HMGB1 is significantly upregulated in gastric mucosal diseases, and upon upregulation, HMGB1 acts as a potent chemokine, triggering the infiltration of inflammatory immune cells and increasing the progression of gastric mucosal diseases ( 40 , 160 ).…”
Section: The Expression Pattern and Functional Role Of Hmgb1 In The S...mentioning
confidence: 99%